Sporadic Coexistence of Multiple Trichoepitheliomas and Solitary Neurofibroma: Mimicking Brooke–Spiegler Syndrome - Rivano Frits Henry Pandaleke; Shienty Gaspersz; Ferra Olivia Mawu; Tara Sefanya Kairupan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The simultaneous presentation of multiple adnexal tumors and neural sheath tumors on the face typically heralds a genodermatosis, most notably Brooke–Spiegler syndrome (BSS) or neurofibromatosis type 1 (NF1). The sporadic, non-syndromic coexistence of these entities in the same anatomical region is a diagnostic pitfall that challenges the principle of parsimony. Case presentation: We report the case of a 24-year-old Asian female presenting with a 12-month history of 18 disseminated, skin-colored papules restricted to the centrofacial region, followed by the rapid development of a 3.0 cm solitary tumor on the right buccal region. Dermoscopic evaluation revealed a dichotomy in tumor morphology: the papules exhibited ivory-white backgrounds with multiple rosette signs and milia-like cysts, while the buccal tumor displayed a structureless pink pattern with absence of pigment networks. Detailed physical examination ruled out cutaneous stigmata of NF1. Histopathological analysis confirmed the diagnosis of multiple trichoepitheliomas and a solitary localized neurofibroma based on characteristic morphological features, including papillary mesenchymal bodies and mast cell presence. Immunohistochemistry was not utilized due to setting-specific resource limitations. Conclusion: This case underscores the potential for sporadic benign tumors to mimic syndromic phenotypes (phenocopies). It highlights the critical importance of recognizing key hematoxylin and eosin morphological markers and clinical signs to establish accurate diagnoses in resource-limited settings where molecular genetics and immunohistochemical staining are unavailable.